Going from microbial ecology to genome data and back: studies on a haloalkaliphilic bacterium isolated from Soap Lake, Washington State - Mormile, Melanie R. (Frontiers in Microbiology, 2014)
Soap Lake is a meromictic, alkaline (∼pH 9.8) and saline (∼14–140 g liter-1) lake located in the semiarid area of eastern Washington State. Of note is the length of time it has been meromictic (at least 2000 years) and the extremely high sulfide level (∼140 mM) in its monimolimnion. As expected, the microbial ecology of this lake is greatly influenced by these conditions. A bacterium, Halanaerobium hydrogeniformans, was isolated from the mixolimnion region of this lake. Halanaerobium hydrogeniformans is a haloalkaliphilic bacterium capable of forming hydrogen from 5- and 6-carbon sugars derived from hemicellulose and cellulose. Due to its ability to produce hydrogen under saline and alkaline conditions, in amounts that rival genetically modified organisms, its genome was sequenced. This sequence data provides an opportunity to explore the unique metabolic capabilities of this organism, including the mechanisms for tolerating the extreme conditions of both high salinity and alkalinity of its environment.